Contraceptive practices and pregnancy intendedness among pregnant adolescents - Lanjakornsiripan W; Amnatbuddee S; Seejorn K; Werawatakul Y; Kleebkaow P; Komwilaisak R; Luanratanakorn S (Dove Medical Press, 2015)
Wakul Lanjakornsiripan, Siriruthai Amnatbuddee, Kanok Seejorn, Yuthapong Werawatakul, Pilaiwan Kleebkaow, Ratana Komwilaisak, Sanguanchoke Luanratanakorn Department of Obstetrics and Gynaecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand Background: Adolescent pregnancy is a major health problem in many developing countries.Objective: To assess contraceptive practices and pregnancy intendedness in pregnant adolescents.Materials and methods: This study was prospectively conducted from September 2013 to June 2014. All consecutively pregnant women between 15 and 19 years old attending the Antenatal Clinic at Srinagarind Hospital and the Khon Kaen Branch of the Planned Parenthood Association of Thailand were invited for participation. Face-to-face interviews by trained interviewers using standardized questionnaires were carried out. Logistic regression was used to determine an adjusted odds ratio (aOR) and 95% confidence interval (CI) of independent predictors.Results: Two hundred participants were enrolled. Mean age was 17.2 years. One hundred and eighteen (59.0%) were currently in school. Seventy-five (37.5%) participants had never used any contraceptive methods. Of the 125 participants who had ever used contraception, regular use of contraceptives was reported in only 21 participants (16.8%). Only two participants (1.0%) had ever used an intrauterine device or implant. Participants’ age was a significant independent factor associated with non-use of contraceptives (aOR, 6.42; 95% CI, 2.94–14.04). Of the 200 participants, 132 (66.0%) declared that the pregnancy was unintended. Significant independent factors predicting unintended pregnancy were educational status (aOR, 6.17; 95% CI, 3.27–13.75) and participants’ age (aOR, 5.76; 95% CI, 2.42–13.70).Conclusion: Non-use and use of contraceptive methods with high failure rates were major reasons leading to adolescent pregnancies. Participants’ age was an independent factor predicting non-use of contraceptives. Educational status and age of the participants were significant factors predicting unintended pregnancy. Keywords: contraception, unintended pregnancy, teenage pregnancy